Student’s Perception of the Use of English in Internship Programs: Real-life Reflections - Wicaksono, Julien Arief; Indrastana, Nodistya Septian; Novawan, Adriadi; Rinda, Renata Kenanga (P3M Politeknik Negeri Jember, 2025)
Internship programs are expected to give many benefits to the students with the real-work experience. For students from English department, this program will be a perfect time to practice and sharpen their English proficiency as well as their capabilities in interacting and communicating with other. This recent study is trying to elicit and elaborate the students’ perspectives toward the use of English during their internship programs. A qualitative case study method was used in this research by interviewing two students who had finished doing internship program in international resorts. Moreover, their internship journal reports were used as secondary data to complete the interview. Then, the analysis of the data was done using thematic analysis. The analysis of the findings has revealed four themes regarding with their opinions on: (1) real-life English use, (2) communication challenges and strategies, (3) gaps between classroom instruction and workplace realities, and (4) suggestions in English instruction.